The Impact of Corporate Governance, Financial Performance, and Technology Investment on Firm Value of Listed Companies in The Stock Exchange of Thailand - Salaphai, Tassawan; Kannarapong, Nathaphon; Somnuek, Sumalee; Yampaka, Tongjai (Rajapark Journal, 2024)
This research aims to investigate the impact of corporate governance (CG), financial performance (ROA), and IT investment on firm value (Tobin's Q) using a quantitative approach. Data from 935 listed companies on the Stock Exchange of Thailand between 2018 and 2022 were analyzed using descriptive statistics, percentages, means, Pearson correlation coefficients, and multiple regression analysis. The results reveal that the average CG score was 86.63, the average ROA was 23.34%, the average IT investment was 0.26, and the average Tobin's Q was 1.03. Multiple regression analysis shows that CG, ROA, and IT investment significantly impact firm value at the 0.01 significance level. The finding that IT investment has a positive impact on firm value is a novel contribution, as technology can enhance operational efficiency, reduce costs, increase revenue, and project a modern image, all of which contribute to firm value and reflect investor expectations for the firm's future. Investors or firms can utilize the model developed in this study to analyze and make informed decisions regarding IT investments. Based on empirical evidence, the researchers substituted values into the equation and found that the prediction accuracy of the equation was 16.2%. The remaining 83.8% may be attributed to other factors influencing firm value.